THE EFFECTS OF PRE-QUESTION STRATEGY ON THE READING COMPREHENSION ACHIEVEMENT OF THE SECOND GRADE STUDENTS AT SMA NEGERI 1 BANTAENG - Awaliah Azis; Rezky Darmayani (Universitas Muhammadiyah Makassar, 2014)
The objective of this research was to find out the significant effect of Pre-question Strategy on the reading comprehension. The strategy employed in this research was Quasi-Experimental method involved two groups of students. The research population was the second year students of SMA Negeri 1 Bantaeng, consisted of the population about 270 students and the sample was 60 students. The sampling strategy used was cluster random sampling strategy. The result of data analysis shows that at the level of significance 0.05 with degrees of freedom (df) = n1 + n2 – 2 where n = 58, there was a significant effect on the reading comprehension of the students who used Pre-questioning strategy. It was proved by the result that the mean score of experimental class (77.7) which was taught used Pre-question was higher than the mean score of control class (55.2), which without Pre-question. The way was t-test value was higher than the t-table value (7.,122,000). It means that an alternative hypothesis was accepted and the null hypothesis was rejected. Based on the result above, the writer draws a conclusion that the using of the Pre-questioning strategy was effective to improve the students’ reading comprehension. Keywords: Reading, Pre-question, strategy, achievement, comprehension